2020
DOI: 10.5014/ajot.2020.74s1-po7208
|View full text |Cite
|
Sign up to set email alerts
|

The Airport Experience for Individuals With Autism Spectrum Disorder (ASD) and Their Caregivers

Abstract: Date Presented 03/28/20 Adaptations and programs in certain airports make air travel easier to tolerate by some individuals with ASD. These programs and adaptations should be replicated and expanded upon in airports throughout the country and ultimately throughout the world. Although airports and organizations are addressing some barriers, this research supports the necessity to create new methods to address the remaining barriers and further facilitate a more enjoyable airport experience for in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…These findings are in line with the results of [ 74 ]’s survey, which showed that in the airport context, the security area is one of the most challenging practices for people with disabilities. In [ 74 ]’s survey, 94.7% of respondents reported finding the security area the most challenging area of the airport experience.…”
Section: Resultssupporting
confidence: 91%
“…These findings are in line with the results of [ 74 ]’s survey, which showed that in the airport context, the security area is one of the most challenging practices for people with disabilities. In [ 74 ]’s survey, 94.7% of respondents reported finding the security area the most challenging area of the airport experience.…”
Section: Resultssupporting
confidence: 91%